STRATEGI KOMUNIKASI MEDIATOR DALAM UPAYA PENCEGAHAN PERCERAIAN DI PENGADILAN LUBUK SIKAPING KABUPATEN PASAMAN - Nora Afrianti; Tomi Hendra (Jurnal Komunikasi, 2025)
In the data from the Lubuk Sikaping Religious Court, the divorce rate data that the author obtained shows that in 2020-2022, namely in 2020 there were 367 divorced couples, in 2021 there were 352 divorced couples and in 2022 there were around 379 divorced couples. only arrived in August. So in total, 1,098 couples divorced in the last 3 years. From the data above, the Lubuk Panggang Religious Court resolves disputes through mediation with the help of a neutral third party. As happened at the Lubuk Suhuing Religious Court which implemented mediation as a way to resolve cases. Therefore, there is a need for a mediator communication strategy to resolve household problems.The aim is to find out what the mediator's communication strategy is in efforts to prevent divorce at the Lubuk Suhuing Religious Court, Pasaman Regency. This type of research uses a qualitative descriptive case study approach which aims to investigate and understand an incident or problem that occurred. In this research the author describes the mediator's communication strategy in efforts to prevent divorce at the Lubuk Suhuing Religious Court, Pasaman Regency. In collecting data the author used observation, interviews, documentation and files/data obtained from the Lubuk Suhuing Religious Court, Pasaman Regency.The results of this research show that the mediator's communication strategy in efforts to prevent divorce at the Lubuk Suhuing Religious Court, Pasaman Regency is that the mediator when carrying out the mediation process with the disputing parties. Negotiation Theory communication strategy from a book by Nic Peeling that negotiation theory is the preparation stage, sharing stage, bargaining stage and closing and commitment stage.